Financialization, premature deindustrialization, and instability in Latin America. (October 2021) - Caldentey, Esteban Pérez; Vernengo, Matías
Abstract : The paper analyses the relation between premature deindustrialization in Latin America and what is termed premature financialization. Premature financialization is defined as a turn to finance, organized as an industrial concern, which is a vehicle for accumulation before the process of industrialization has reached maturity. This contrasts with developed countries where financialization occurs after an advanced stage of economic and social development has been reached, and where the growth of the financial sector, beyond a certain threshold, can be detrimental to economic activity. The paper examines the consequences of premature financialization for investment, growth, and financial stability.